Assessing children’s empathy through a Spanish adaptation of the Basic Empathy Scale: parent’s and child’s report forms - Sánchez-Pérez, Noelia; Fuentes, Luis J.; Jolliffe, Darrick; González-Salinas, Carmen (Frontiers in Psychology, 2014)
The aim of the current research was to study cognitive and affective empathy in children aged 6 to 12 years old, and their associations with children’s family environment and social adjustment. For this purpose, we developed the Spanish version of the Basic Empathy Scale (BES), self- and parent-report forms. Factorial analyses confirmed a two-component model of empathy in both self- and parent-report forms. Concordance between parent-child measures of empathy was low for cognitive and affective factors. Analyses of variance on the cognitive and affective components brought a significant effect of age for self-reported Cognitive Empathy, with older children scoring higher than younger ones. Gender brought out a significant principal effect for self-reported Affective Empathy, with girls scoring higher than boys. No other main effects were found for age and gender for the rest of the factors analyzed. Children’s empathy was associated with socioeconomic status and other family socialization processes, as well as children’ social behaviors. Overall the new measures provided a coherent view of empathy in middle childhood and early adolescence when measured through self and parent reports, and illustrate the similarity of the validity of the BES in a European-Spanish culture.